The Community Development Operation Model of Ban Nam Sai Community, Thung Benja Sub-district, Tha Mai District, Chanthaburi Province - Luengalongkot, Pongsatean (Community and Social Development Journal, 2023)
Community development operations are important because they help strengthen communities. The objectives of this research were to analyze and examine the consistency of the community development operations (CDO) model with empirical data, and to study the weight of direct, indirect, and total effect of factors influencing on CDO of Ban Nam Sai Community, Thung Benja Sub-district, Tha Mai District, Chanthaburi Province. The population in this study was 173 people who are representing households living in Nam Sai Village. The samples were 121 people, calculating by Taro Yamane’s formula. The research tool in this study was the questionnaire-based survey. Analyzed and examined the consistency of the community development model of Ban Nam Sai community with empirical data based on the model goodness of fit indices used a Structural Equation Model. Analyzed weight of direct, indirect and total effect of causal factors on community development operation of Ban Nam Sai community by used a Structural Equation Model with statistic Path analysis. The results were found that The CDO model of Ban Nam Sai community developed consistent with the empirical data. It was also found that Leadership, public participation and community communication had direct effects on community development operations of Ban Nam Sai community. Besides, community communication was found a direct effect on public participation. Among these studied variables, leadership was found to have an indirect effect on community operations of Ban Nam Sai Community through public participation and community communication. Community communication also had an indirect effect on the community development operation of the Ban Nam Sai community through public participation. The total effect on community development operations of Ban Nam Sai community. The highest total influential factor was public participation, followed by leadership and community communication respectively. Suggestion from the research results, the community development operation model of Ban Nam Sai Community is suitable for use. The model should be developed and applied to use to the similar context of communities/villages for further community development.